The effects of metformin on the bone filling ration around of TiAl6Va4 implants in non diabetic rats - Yıldırım, Tuba Talo; Dündar, Serkan; Bozoğlan, Alihan; Karaman, Tahir; Kahraman, Onur Evren; Özcan, Erhan Cahit (Elsevier B.V., 2020)
Objectives: In this research it was aimed to that evaluation of the effects of systemic metformin administration on the periimplant bone tissue response of TiAl6Va4 implants in experimental rat model. Materials and method: Firstly TiAl6Va4 implants were inserted surgically in the metaphyseal part of the tibial bone and after, the rats were randomly separated into two groups: Controls (CNT) (n = 10) and Metformin group (M) (n = 10). No additional treatment was applied to the controls during the 4-week experimental period. Rats received 40 mg/kg metformin in every day during the four week experimental period in M group. At the end of the 28-day follow-up period, the TiAl6Va4 implants with surrounding bone were used for the histopathologic analysis. To analysis of the datas between M and CNT Student-T Test was used. Result: Periimplant bone tissue filling ratios (%) were detected higher in M group compared with the CNT (P < 0.05). Conclusion: Systemic administration of metformin may increases titanium implant osseointegration in non-diabetic rats. © 2020
Keywords: Bone filling; Dental implant; Metformin; Osseointegration